Media, Communication and the Struggle for Democratic Change 2019
DOI: 10.1007/978-3-030-16748-6_4
|View full text |Cite
|
Sign up to set email alerts
|

Peace, But at What Cost? Media Coverage of Elections and Conflict in Kenya

Abstract: translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific statement, that such names are exempt from the relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Traditionally, ethnic identity defines voting patterns, and Kenyan elections often involve political parties created through (temporary) coalitions or consensus of ethnic communities (Bratton and Kimenyi, 2008). Ethnic rivalry combined with mistrust of institutions – like the courts and election agencies – intermittently results in violence, especially among the urban and rural poor populations (Cheeseman et al, 2019).…”
Section: The Rise Of Peaceocracymentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, ethnic identity defines voting patterns, and Kenyan elections often involve political parties created through (temporary) coalitions or consensus of ethnic communities (Bratton and Kimenyi, 2008). Ethnic rivalry combined with mistrust of institutions – like the courts and election agencies – intermittently results in violence, especially among the urban and rural poor populations (Cheeseman et al, 2019).…”
Section: The Rise Of Peaceocracymentioning
confidence: 99%
“…The campaigns were meant to forestall violence during the elections in 2007 (Lynch, 2020: 2). Since then, political scientists and journalism scholars have suggested that peaceocracies are emerging in several other post-conflict nations (Lynch, 2020; Cheeseman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The interests of the two parties are mostly intertwined—and use the publications as tools to further their interests (Nyanjom, 2012). For example, the Aga Khan, the owner of the Daily Nation has traditionally maintained close connections with the government of the day (Cheeseman et al, 2019; Makokha, 2010). The Standard is owned by former President Daniel Moi family, while the People Daily is associated with former President Uhuru Kenyatta.…”
Section: The Kenya Newspapers Industrymentioning
confidence: 99%
“…Makokha (2010) points out that the politico-economic elite use these platforms to control the overall editorial, strategic, and political direction of the newspapers. In this vein, Cheeseman et al (2019) argue that the political networks and leaning of media owners, which follow both ethnic and personal network and political calculations, have had significant influence in the reporting of political affairs. Thus, the nature of print media ownership explains why there is no media differentiation in Kenya’s newspaper industry.…”
Section: The Kenya Newspapers Industrymentioning
confidence: 99%
“…Political elites often mobilize against each other in ever-shifting ethnic alliances, sparking political conflicts that sometimes result in violence (Kagwanja 2009). Yet politicians also frequently speak an ethnically and religiously inclusive language, promising to safeguard peace, development, and national unity in exchange for loyalty (Long et al 2013;Cheeseman, Ouma and Maweu 2019;Willis, Cheeseman and Lynch 2014). In these dynamics, women are frequently seen as dependent on men and excluded from political spheres.…”
Section: Youth Violence and Religion In Kenyamentioning
confidence: 99%